The introduction of a tunnel borer into a South African gold mine - J. G. Taylor; R. N. Taylor; A. E. Hall (The Southern African Institute of Mining and Metallurgy, 1978)
The introduction of tunnel-boring machines to South African gold mines has created problems and challenges which accompany any new technique. This paper describes the experience gained in this field, especially in the design and erection of a tunnel borer and in boring and environmental conditions.